Loan loss provisions, earnings management, capital management, and signalling: the case of Vietnamese banks. (2nd December 2021) - Le, Tu D.Q.; Nguyen, Liem T.; Tran, Son H.
This study examines loan loss provision (LLP) behaviours of Vietnamese banks between 2006 and 2015. The findings show that earnings management is positively related to LLP regardless of the restructuring period, suggesting that LLPs can be used by Vietnamese banks as a mechanism for aggressive earnings management. There appears to be no capital management before the restructuring period. However, the findings indicate that Vietnamese banks use capital management with LLP during the restructuring period. Furthermore, the positive relation between LLP and future earnings during the restructuring period suggests that investors may view an abnormal increase in LLP as a signal of loan quality. The findings further demonstrate that LLP is positively associated with bank inefficiency, credit growth, bank size, and lending specialisation. State-owned commercial banks are found to reserve a greater level of provisions compared to privately owned commercial banks. Based on the research findings, we offer several implications for relevant stakeholders.